Some properties of finite dimensional fuzzy anti-normed linear spaces (Baghdad Science Journal, 2020)
In this paper the definition of fuzzy anti-normed linear spaces and its basic properties are used to prove some properties of a finite dimensional fuzzy anti-normed linear space.